Deciphering three diplomatic letters sent by Maximilian II in 1575. Issue 2 (4th March 2022) - Kopal, Nils; Waldispühl, Michelle
Abstract: This article presents three newly rediscovered encrypted Habsburg letters that were sent by Maximilian II to his Polish delegates in 1575. We describe the process of deciphering and the principles and peculiarities of the cipher from a cryptographic perspective. Furthermore, content and historical and linguistic context of the letters are explained. The records are held at the Österreichisches Haus-, Hof- und Staatsarchiv and were collected and deciphered in the context of the interdisciplinary and international research project "DECRYPT – Decryption of historical manuscripts". For cryptanalysis the open-source e-learning program CrypTool 2 was used. The article is the result of a joint effort of a computer scientist and a historical linguist.